Experimental Analysis of Eccentric Compression Performance of Larch Wood-Steel Composite Columns - Junren Wang; Shaowei Duan; Jiewei He; Zhifeng Wang (Advances in Civil Engineering)
In this paper, a new steel-wood composite column with an H-shaped section was proposed. In order to form an H-shaped cross section, a larch board is fixed on the outer surface of the left and right edges of a hot-rolled H-beam by using physical connection. When the eccentricity is the same, eccentric compression tests were carried out on two types of columns by changing the thickness of the larch board, cross-sectional area of the hot-rolled H-beam, and slenderness ratio in composite columns. Therefore, type A is joined by structural glue only with the larch board and hot-rolled H-beam, and type B is joined by both structural glue and bolts. With the variation of strain and deflection, failure process and failure modes of the hot-rolled H-beam and larch from composite columns under various loads were observed, and the ultimate bearing capacity and stability of composite columns were studied. The test results showed that the overall working performance of the hot-rolled H-beam and larch board was good, and the stability of the hot-rolled H-beam column could be effectively improved. With the increase of wood thickness, cross-sectional area of the hot-rolled H-beam, slenderness ratio of composite columns, and the bearing capacity of the specimens were increased. Moreover, a simplified formula was proposed by the superposition principle. The theoretical analysis accorded with the experimental results, thus providing a reference basis for further study and application of similar steel-wood composite columns.